Pengaruh Stretching Dan Strengthening Terhadap Penurunan Skala Nyeri Sendi Lutut Ostheoarthritis Genu Di Kwala Bekala Lingkungan XIV Medan - Andre Mulyadi Ginitng; Wahyu Wijanarko; Ronald Erwansyah (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Osteoarthritis or often called degenerative joint disease is a cartilage disorder characterized by clinical, histological, and radiological changes. Osteoarthritis most commonly occurs in the knees, hips, spine, and ankles. One that often occurs in the quadriceps muscle is a muscle in the knee joint that functions as an active stabilization of the knee joint and also plays a role in the wrist joint. as an active stabilizer of the knee joint and also plays a role in the wrist joint. Objective: To determine the effect of pain degree on knee joint reduction in Osteoarthritis Genu patients, to determine the scale of Osteoarthritis knee joint pain after stretching & strengthening. Methods: This research is a quasi-experimental study (quasi-experimental) with pre and post test one group design. Before and after being given treatment, the sample was measured using the NRS scale first to assess the basic functional ability of the patient's knee (undiastirin, 2010). Result: -4.850 because the ASYMP SIG value (P VALUE) > 0.05, the data affect the ability of knee functional activity in knee osteoarthritis patients in Kwala Bekala Village XIV Environment Medan. Conclusion: Based on the results of research and discussion, it can be concluded that there is an effect of stretching and strengthening on reducing knee joint pain scale in Osteoarthritis Genu.Keywords: Pain, joints, knees